2016
DOI: 10.1161/circgenetics.115.001274
|View full text |Cite
|
Sign up to set email alerts
|

RP1-13D10.2 Is a Novel Modulator of Statin-Induced Changes in Cholesterol

Abstract: Background Numerous genetic contributors to cardiovascular disease risk have been identified through genome-wide association studies (GWAS); however, identifying the molecular mechanism underlying these associations is not straightforward. The JUPITER trial of rosuvastatin users identified a sub-genome wide association of rs6924995, a SNP ~10kb downstream of MYLIP (aka IDOL, inducible degrader of LDLR), with LDL cholesterol statin response. Interestingly, though this signal was initially attributed to MYLIP, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…This work follows several other examples of noncoding RNAs such as miRNAs that regulate both cholesterol efflux and LDL-C uptake in vivo, such as miR-33, miR-148a, and others, 10 as well as fewer examples of lncRNAs that have been shown to regulate lipoprotein metabolism. 11 However, this study by Mitchel et al 6 is among the first to show a genetic polymorphism within a lncRNA that modulates its expression and affects its downstream effects with regard to lipid homeostasis.…”
Section: Article See P 223mentioning
confidence: 88%
See 4 more Smart Citations
“…This work follows several other examples of noncoding RNAs such as miRNAs that regulate both cholesterol efflux and LDL-C uptake in vivo, such as miR-33, miR-148a, and others, 10 as well as fewer examples of lncRNAs that have been shown to regulate lipoprotein metabolism. 11 However, this study by Mitchel et al 6 is among the first to show a genetic polymorphism within a lncRNA that modulates its expression and affects its downstream effects with regard to lipid homeostasis.…”
Section: Article See P 223mentioning
confidence: 88%
“…A report by Mitchel et al 6 in this issue of Circulation Cardiovascular Genetics highlights this complexity in an effort to identify the mechanism governing the association of a SNP, rs6924995, at the MYLIP gene locus to statin responsiveness in LDL-C lowering. The authors explored the mechanism governing the sub-GWAS significant association of a SNP identified in a previous GWAS for statin effects on LDL-C lowering by the Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) investigators.…”
Section: Article See P 223mentioning
confidence: 99%
See 3 more Smart Citations